Pengaruh Kemudahan Navigasi, Kualitas Pelayanan, Pengalaman Konsumen Terhadap Loyalitas Konsumen pada Platform Pesan Antar Makanan (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the influence of navigation ease, service quality, and consumer experience on consumer loyalty in digital food delivery platforms in Indonesia. The research employed a quantitative method using the Structural Equation Modeling approach with Partial Least Squares (PLS-SEM). Data were collected from 233 active users of services such as GoFood, GrabFood, and ShopeeFood, aged between 17–35 years. The results show that navigation ease, service quality, and consumer experience significantly affect user confirmation, which in turn impacts perceived usefulness, satisfaction, continuance intention, and consumer loyalty. Consumer experience had the greatest influence on confirmation, while continuance intention showed the strongest effect on loyalty. This study highlights the importance of enhancing user experience and digital service quality to sustain long-term consumer loyalty.